2016
DOI: 10.4103/0972-124x.176392
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relation between anemia and periodontitis by estimation of blood parameters: A cross-sectional study

Abstract: Background:Anemia of chronic disease is defined as anemia occurring in chronic infections, inflammatory conditions, or neoplastic disorders which are not due to marrow deficiencies or other diseases, and occurring despite the presence of adequate iron stores and vitamins.Aims:To evaluate the relation between anemia and periodontitis by estimation of blood parameters and to assess whether periodontitis like other inflammatory conditions can lead to anemia. It is a randomized controlled clinical trial.Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 15 publications
2
19
1
Order By: Relevance
“…Similar results in MCV were seen in other studies [37][38][39]. A decrease in MCH value is seen in microcytic anemia caused due to iron deficiency, whereas an increase in MCH value is seen in macrocytic anemia caused by vitamin deficiency.…”
Section: Discussionsupporting
confidence: 77%
“…Similar results in MCV were seen in other studies [37][38][39]. A decrease in MCH value is seen in microcytic anemia caused due to iron deficiency, whereas an increase in MCH value is seen in macrocytic anemia caused by vitamin deficiency.…”
Section: Discussionsupporting
confidence: 77%
“…Hb, RBC counts, hematocrit (HCT), mean corpuscular volume (MCV), mean corpuscular Hb (MCH), mean corpuscular Hb concentration (MCHC), and erythrocyte sedimentation rate (ESR) (Hutter et al, 2001;Gokhale et al, 2010;Naik et al, 2010;Prakash et al, 2012;Chakraborty et al, 2014;Kolte et al, 2014;Patel et al, 2014;Khan et al, 2015;Latha et al, 2015;Anumolu et al, 2016;Carvalho et al, 2016;Nibal et al, 2019).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Furthermore, a study by Anumolu et al . () found reduced haemoglobin and erythrocyte counts and concluded that periodontitis encourages anaemia (Anumolu et al, ). Similar results were found in the previous investigation by this working group (Ziebolz et al, ).…”
Section: Discussionmentioning
confidence: 99%